COLLABORATIVE METHODS IN TEACHING ENGLISH IN TECHNICAL UNIVERSITIES AND THE SPECIFICS OF ITS APPLICATION - Rasulova, Zukhra (Журнал иностранных языков и лингвистики, 2023)
This article discusses the features of collaborative methods in teaching English in technical universities. In this regard, project and case assignments give students the opportunity to practice language skills in meaningful contexts that often mimic real-life tasks and situations. But it should be organized in collaboration with subjects that refer future specialists to their profession they are going to occupy. Methods applied during their lessons must train the students to survive in different situations they can come across in their professional sphere. Grammatically appropriating and organizing lexical based lesson only can give expected results in this issue. Even a little slip or omission in lesson design can lead a researcher to a great confusion. Grammar and lexical training should be matched fully.